2010
DOI: 10.1021/es102273t
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Iron Use in Societal Evolution

Abstract: A dynamic material flow model was used to analyze the patterns of iron stocks in use for six industrialized countries. The contemporary iron stock in the remaining countries was estimated assuming that they follow a similar pattern of iron stock per economic activity. Iron stocks have reached a plateau of about 8-12 tons per capita in the United States, France, and the United Kingdom, but not yet in Japan, Canada, and Australia. The global average iron stock was determined to be 2.7 tons per capita. An increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 24 publications
3
131
1
Order By: Relevance
“…24 From previous work 22 we indentify two different patterns of in-use-stocks of steel: a) a saturation after a certain time at a level of (10±2) ton/cap as seen in the US, the UK, and France and b) a continued linear growth in time as seen in Japan, Australia, and…”
Section: Parameter Estimation and Scenario Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…24 From previous work 22 we indentify two different patterns of in-use-stocks of steel: a) a saturation after a certain time at a level of (10±2) ton/cap as seen in the US, the UK, and France and b) a continued linear growth in time as seen in Japan, Australia, and…”
Section: Parameter Estimation and Scenario Analysismentioning
confidence: 95%
“…This reflects the slackness of the residential building stock better than a normal distribution. Based on previous studies, 22 We propose a set of 6 simple scenarios to depict future development. An overview on the major parameters is included in Figure 2.…”
Section: Parameter Estimation and Scenario Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Müller et al 36 showed that iron use appears to have reached a plateau of 8-12 t per capita in France, the United Kingdom, and the United States ( Figure 3 ). In other countries, a plateau has yet to be reached.…”
Section: Evolutionary Demand Changementioning
confidence: 99%
“…This has given rise to a literature on the analysis of material stocks, including steel stocks in various nations [8], steel in the building stock [9] and materials in housing [10]. Evidence that per capita requirements for steel stocks saturate at around 10 tonnes per person [8] suggests that developed economies such as the UK could feasibly operate a closed-cycle for steel, whereas developing economies such as China and India cannot do this until their stocks have grown further. -Material substitution: Ashby [11] provides an evidence base for examining the potential for using materials other than those commonly used today.…”
Section: Motivations For Materials Efficiencymentioning
confidence: 99%